Use Of Anti-Epileptics For Seizure Prophylaxis After Traumatic Brain Injury In The Pediatric Population - Khan, Aroosh; Muntaha, Sidra Tul; Ayaz, Hammad; Tariq, Afrah; Mughal, Huma (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the frequency of Early Post-Traumatic Seizures (EPTS) in patients receiving anti-epileptic prophylaxis after moderate to severe traumatic brain injury (TBI) in children. Methods: A Descriptive Case Series was conducted at the Department of Neurosurgery, Shifa International Hospital Islamabad from 26 August 2021 to 25 August 2022. A total of 160 children aged from 2 to 18 years who presented with traumatic brain injury within 24 hours of trauma were included. Patients were given intravenous phenytoin in a loading dose of 20mg/kg with the rate of 1-2mg/kg/min infusion followed by a daily maintenance dose of 5mg/kg twice daily. Patients were clinically monitored for the occurrence of seizures during the first 7 post-traumatic days. Diagnosis of early post-traumatic seizures was made by a consultant neurologist as per operational definitions. All the study-relevant information was noted on the proforma. Data entry and analysis was done using SPSS version 24.0. Results: In 160 patients mean age and duration of injury were 8.45±4.54 years and 7.91±4.93 hours respectively. Male to female incidence was 92 (57.50%) and 68 (42.50%) respectively. Early post-traumatic seizures were seen in 17 (10.63%) patients. Conclusion: EPTS occurred in 10.63% of children with moderate to severe TBI despite Phenytoin prophylaxis. In our view, phenytoin prophylaxis should be given to all children with traumatic brain injury to reduce the incidence of early seizures. Keywords: Early posttraumatic seizures, Phenytoin, Traumatic brain injury.